Association between Lysholm score and muscular torque deficit after anterior cruciate ligament reconstruction. (2nd July 2020) - de Andrade, André Luis Lugnani; Castro, Alex; Livani, Bruno; Belangero, William Dias
Purpose: The asymmetry of muscular strength after anterior cruciate ligament reconstruction (ACLR) is associated with increase in the development of new lesions. This asymmetry is precisely assessed by isokinetic dynamometry which is a high-cost technique, limited to major centers and hospitals. Thus, the aim of this study was to test the accuracy of one of the most frequently used functional questionnaires, the Lysholm score, to diagnose the knee torque deficit. Methods: In total, 115 patients were evaluated after ACLR. Knee symptoms were evaluated using the Lysholm questionnaire and knee extensor and flexor peak torque during maximal isokinetic concentric contractions at 60° s −1 (5 repetitions) and 180° s −1 (15 repetitions). Patients with <20% peak torque deficit were considered symmetric (normal). Results: An increase in the Lysholm score was associated with a deficit reduction in the peak torque of knee extensors at 60° s −1 ( r = −0.294) and 180° s −1 ( r = −0.297) ( p < 0.05 for both). Cutoff Lysholm scores of >90 points for 60° s −1 allowed the correct diagnosis of symmetry in 71% and of >89 points for 180º·s −1 allowed the correct diagnosis of symmetry in 73%, for knee extensors. Patients with a Lysholm score of >89 points presented an isokinetic deficit 36% lower than patients with a Lysholm score of ≤89 points ( p < 0.05). Conclusion: A Lysholm score of >89 points has predictive value for deficits in the peak torque of knee extension (<20%). However, replacement of the isokinetic evaluation by this instrument must be performed with caution because of its accuracy.